INTRODUCTION TO THE SPECIAL ISSUE - OGAR , Joseph Nkang (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2026)
This special issue of GNOSI is a tribute to a man who was not only the founding Editor in Chief of this journal but also a philosopher, a mentor, and a friend to many. Professor Asira E. Asira passed away after a life devoted to the pursuit of wisdom and the cultivation of young minds. His absence is felt deeply across the University of Calabar, the Department of Philosophy and Leadership Studies, and the wider scholarly community. With this volume, we honour his memory by doing what he loved most: engaging seriously with the hardest questions of human existence, especially those concerning death, personhood, and what it means to live well in the face of mortality.